IMPLEMENTASI SUPERVISI KLINIS DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SEKOLAH DASAR - Desi Agustini; Istikomah Istikomah; Mochamad Sultoni (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Background this study was carried out to improve the teaching and learning process is carried out by teachers through a series of systematic improvements to increase the competence of professionals. This journal aims to find out the clinical supervision program, stages of implementation of the clinical supervision, and supporting factors as well as a barrier. This research was carried out in accordance with measures of clinical supervision according to Sergiovany in Kristiawan (2019), namely; 1) meeting before observation; 2) supervisors observing teachers; 3) analysis and strategy; 4) meeting after observations; 5) analysis of activities after the observation. Results to be achieved are able to enhance the professionalism of teachers in order to solve problems and overcome barriers in SDN 9 Island Rimau through clinical supervision.